Application of GIS in pig production system in Nigeria - Taiwo Omodele, Isaiah Annayochukwu Okere, Mutiu Olakunle Oladele-Bukola, Adeboye Joseph Omole ,Ajoke Oyegbami (African Journal of Pig Farming, 2023)
This study aimed to identify the pig producers across various administrative regions and to determine the pig production system in Nigeria through an intensive survey of pig farms with the use of Global Positioning System (GPS). Categorization of farms by proportion in Nigeria showed that 81.1% of states had very low (<5) and low (5 to 50) number of pig farms, 8.1% of states had medium (50 to 100) number of pig farms and 10.8% of states had high (100 to 150) and very high (>150) number of pig farms. In Nigeria, there are two separate pig production systems: small and medium scales. The small scale system is essentially characterized by very low to low scale of production. Analysis of categories of production in Nigeria showed that 45.9% of states recorded very low (<100 pigs) and low (100 to 1,000 pigs) scales of production, 46% of states were in the medium (1,000 to 10,000 pigs) scale of production and 8.1% of states had high (10,000 to 100,000 pigs) and very high (>100,000 pigs) scales of production. GIS qualitative analysis showed that in the North, the production classes: very low, low, medium, high and very high scales of production by states were 40, 30, 25, 0 and 5%, respectively while in the South, the production classes were 0, 17.6, 70.6, 11.8 and 0%, respectively. A high number of Northern states were identified in the low category of pig production scales while most Southern states were in the medium category. The application of GIS revealed that the pig sector in Nigeria is dominated by small and medium scales of production while the harsh climate and its future change pose a major threat to pig farming in the Northern Nigeria.